(3eMGVQGJ heSGFd eMdhdI hab GdfXGe GdeMGSHj GdeGdj hGdeYGjjQ GdeMGSHjI GdOhdjI s - (3eMeO GdTQja(B, (3Hf RGhjs ((3GdLRGFQ (B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2018)
(3JfGhd GdcJGH LRAG gGeG ef eMGSHI GdTQcGJ HGdJQcjR Ydi KdGKI CfhGY ef GdTQcGJ JeKdJ aj TQcGJ GdJVGef, GdTQcI PGJ GdeSDhdjI GdeMOhOI hTQcI GdeSGgeI , hbO OYeJ gPg GdaUhd HJWHjbGJ heSGFd eMdhdI MJi jSgd Ydi GdWGdH hGdHGMK age eNJda GdeYGdLGJ GdeMGSHjI GdeecfI (B.s
(3GdeQGLY U(B.217s
Keywords: (3GdTQcGJ (B- (3eMGSHIs; (3GdeYGjjQ GdeMGSHjIs